Ships and men in the late Viking Age : the vocabulary of runic inscriptions and skaldic verse - Jesch, Judith, 1954- (Boydell Press, 2001)
Names of ships; The ship and its parts; The hull; The stems; Inside the hull; Rudders, oars and shields; Masts, sails and rigging; In harbour and on land; The vocabulary of sailing; Description and metaphor; Preparing and launching; The ship in the sea; Shipwreck and landing; 5 The Crew, the Fleet and Battles at Sea; Manning a ship; The owner; The captain; The crew; The fleet and the troop; lið; Compounds with -lið; floti; leiðangr; The troop; Units of the fleet; Summary; Battles at sea; Maritime warfare; Place and time; Preliminaries to battle; Bringing the ships together.